Consumer Intention To Switch From Conventional Money To E-Money - Ariska, Ricky Angga; Waskita, Johan Paing Heru; Purwitasari, Fadilla (Faculty of Economic and Business Wijaya Kusuma Surabaya University, 2023)
The development of electronic payments, also known as non-cash transactions, is greatly influenced by advances in technological development and changes in people's lifestyles. Currently, the development of non-cash payment instruments is running very rapidly and has a big impact on buying and selling transactions. With the support of increasingly advanced technology, people who use and provide non-cash payment system services are continuously looking for alternative non-cash payment instruments that are more efficient and safe. This research discusses the factors that influence consumers in switching from using conventional money to e-money. Research subjects are people who have e-money and have made transactions using e-money. The research object is all types of e-money used in Indonesia legally according to Indonesian regulations. The variables used in this research are Compatibility Factor, Convenience Factor, and Perceived Content Factor. The sample was determined using purposive sampling with the criteria of students at the Faculty of Economics and Business, Universitas Wijaya Kusuma Surabaya who had an e-money account and had made transactions using e-money at least 3 times. The number of research samples was determined using the Slovin sample calculation. This formula takes into account the known population size. The research sample used was 100 respondents. The analysis techniques used in this research are Validity Test, Reliability Test, Multiple Linear Regression Model Analysis, F Test, and t Test. In the data processing that has been carried out, Compatibility and Perceived Content have an influence in the same direction as Intention to Switch. Meanwhile, Convenience has an influence that is not in the same direction as Intention to Switch. The results of the hypothesis test show that the significant value of Compatibility is 0.000. Convenience is 0.666. Perceived Content is 0.000. This value shows that Compatibility and Perceived Content have an influence on switching behavior to e-money, while Convenience has no influence on switching behavior to e-money.